The Economics of Modern Manufacturing: Technology, Strategy, and Organization - Milgrom, Paul; Roberts, John (American Economic Review, 1990)
Manufacturing is undergoing a revolution. The mass production model is being replaced by a vision of a flexible multiproduct firm that emphasizes quality and speedy response to market conditions while utilizing technologically advanced equipment and new forms of organization. Our optimizing model of the firm generates many of the observed patterns that mark modern manufacturing. Central to our results is a method of handling optimization and comparative statics problems that requires neither differentiability nor convexity.